Syntheses of the hexahydroindene cores of indanomycin and stawamycin by combinations of iridium-catalyzed asymmetric allylic alkylations and intramolecular Diels-Alder reactions - Gärtner, Martin; Förster, Sebastian; Helmchen, Günter (Chemistry - a European journal, 2013)
Short and concise syntheses of the hexahydroindene cores of the antibiotics indanomycin (X-14547 A) and stawamycin are presented. Key methods used are an asymmetric iridium-catalyzed allylic alkylation, a modified Julia olefination, a Suzuki-Miyaura coupling, and an intramolecular Diels-Alder reaction.
First published: 23 November 2012
Gesehen am 21.06.2018